Increasing Risk of Poverty In Central Java Due to The Covid-19 Pandemic - Wuranti, Hayu (Optimum: Jurnal Ekonomi dan Pembangunan, 2022)
The COVID-19 pandemic is a multidimensional crisis that started from a health crisis that eventually caused a global crisis to a global recession. Various efforts have been made by the government to prevent the spread of the Covid-19 virus, including by limiting community activities, which have an effect on decreasing people's income. The purpose of this study is to the factors that influence the increase in the number of poor people in 35 districts/cities in Central Java due to the Covid-19 pandemic in 2020, using multiple regression analysis. The results showed that the variables depicting the number of covid cases, life expectancy, economic growth, and hotel room occupancy rate significantly affected the number of poor people. While partially the four variables simultaneously also significantly affect the number of poor people.